Inhibition of Inflammation and Regulation of AQPs/ENaCs/Na+-K+-ATPase Mediated Alveolar Fluid Transport by Total Flavonoids Extracted From Nervilia fordii in Lipopolysaccharide-induced Acute Lung Injury - Yin, Shuomiao; Ding, Meizhu; Fan, Long; Yu, Xuhua; Liang, Ziyao; Wu, Lei; Gao, Zhiling; Lin, Lin; Chen, Yuanbin (Frontiers in Pharmacology, 2021)
Aims: The occurrence of vascular permeability pulmonary edema in acute lung injury (ALI) is related to the imbalance of alveolar fluid transport. Regulating the active transport of alveolar fluid by aquaporins (AQPs), epithelial sodium channels (ENaCs), and Na+-K+-ATPase can effectively reduce the edema fluid in the alveolar cavity and protect against ALI. We evaluated the therapeutic effects of total flavonoids, extracted from Nervilia fordii (TFENF), and investigated its potential mechanisms of alveolar fluid transport in a rat ALI model. Materials and methods: A model of lipopolysaccharide (LPS, 5 mg/kg)-induced ALI was established in Sprague-Dawley (SD) rats through the arteriae dorsalis penis. SD rats were divided into 6 groups, including the vehicle, LPS model, TFENF (6 mg/kg, 12 mg/kg, 24 mg/kg), and dexamethasone group (DEX group, 5 mg/kg). The wet-to-dry (W/D) lung weight ratio, oxygenation index, and histopathological observation were used to evaluate the therapeutic effect of TFENF. The mRNA expression of AQPs, ENaCs, and pro-inflammatory cytokines was determined using real-time polymerase chain reaction, whereas protein expression was determined using immunohistochemistry. The Na+-K+-ATPase activity was assessed using enzyme-linked immunosorbent assay. Results: LPS significantly stimulated the production of inflammatory mediators including tumor necrosis factor (TNF)-α and interleukin (IL)-1β, and disrupted the water transport balance in the alveolar cavity by inhibiting AQPs/ENaCs/Na+-K+-ATPase. Pretreatment with TFENF reduced the pathological damage and W/D ratio of the lungs and ameliorated the arterial blood oxygen partial pressure (PaO2) and oxygenation index. TFENF further decreased the mRNA level of TNF-α and IL-1β; increased the expression of AQP-1, AQP-5, αENaC, and βENaC; and increased Na+-K+-ATPase activity. Moreover, the regulation of AQPs, βENaC, and Na+-K+-ATPase and the inhibition of TNF-α and IL-1β by TFENF were found to be dose dependent. Conclusion: TFENF protects against LPS-induced ALI, at least in part, through the suppression of inflammatory cytokines and regulation of the active transport capacity of AQPs/ENaCs/Na+-K+-ATPase. These findings suggest the therapeutic potential of TFENF as phytomedicine to treat inflammation and pulmonary edema in ALI.